Forgiveness and Social Support as Protective Factors of Post-Traumatic Stress Symptoms among Women Victims of IPV - Ednadita, Gloryka; Danastri, Monika; Ardelia, Christina; Ramandha, Kamelia; Christia, Mellia (UI Scholars Hub, 2024)
In Indonesia, most cases of violence against women occur as domestic and dating violence, that is, intimate partner violence or IPV. Such cases report relatively more prevalent, severe posttraumatic stress symptoms (PTSS), but studies on protective factors are limited. Therefore, this study examined whether forgiveness and perceived social support among young women who have experienced IPV by former partners negatively predicted PTSS. We used the Posttraumatic Stress Disorder Checklist-5, the Heartland Forgiveness Scale, and the Multidimensional Scale of Perceived Social Support. The study analyzed data from 60 young women (Mage= 22.4) who had experienced IPV that lasted an average of nearly 2 years. Multiple regression analysis showed that forgiveness (r = −0.41, p < 0.01) and perceived social support (r = −0.29, p < 0.05) negatively predicted PTSS. Further results suggested that forgiving the perpetrator and receiving support from a significant other did not predict lower PTSS symptoms (r = 0.20, p > 0.05; r = −0.02, p > 0.05). Thus, fostering forgiveness and social support, but not with the perpetrator, is linked to lessened PTSS for young women.